Corporate Values, Codes of Ethics, and Firm Performance: A Look at the Canadian Context - Donker, Han (Journal of business ethics, 2008)
In this empirical study, we present two new models that are corporate ethics based. The first model numerically quantifies the corporate value index (CV-Index) based on a set of predefined parameters and the second model estimates the market-to-book values of equity in relation to the CV-Index as well as other parameters. These models were applied to Canadian companies listed on the Toronto Stock Exchange (TSX). Through our analysis, we found statistically significant evidence that corporate values (CV-Index) positively correlated with firm performance. The results are even more significant for firms with low market-to-book values. Our empirical findings suggest that corporate ethics is vital for management, employees, shareholders, stakeholders, and the community at large. In addition, we have tested and confirmed five hypotheses that are used to illustrate corporate ethics behavior and performance.